Standardization of Selfdirected Learning Readiness Scale for Nursing and Midwifery Students - Mohammad Reza Ahanchian; Hoshang Garavand; Azam Mohammadzadeghasr; Seyed Ali Akbar Hosseini (Kerman University of Medical Sciences, 2013)
Background & Objective: Selfdirected learning readiness scale (SLRS) proposed by Fisher et al (2001) is a selfevaluation tool containing 50 questions The aim of the present study was to standardize SLRS for use among Nursing and Midwifery students Methods: The statistical population of this descriptive psychometric study included all undergraduate students of Nursing and Midwifery of Mashhad University of Medical Sciences (N = 550) Study samples were 224 students (27% males and 73% females) The research instrument was selfdirected learning readiness scale Validity was confirmed by determining content validity and construct validity (exploratory factor analysis) and reliability was confirmed by calculating the coefficient of internal consistency (Cronbachs alpha) Results: Three factors of s elfmanagement willingness to learn and selfcontrol were extracted from the SLRS that could explain 345% of the total variance Cronbachs alpha for the entire questionnaire and the mentioned factors were respectively 092 088 082 and 079 The ttest results showed no significant difference between male and female students in regard to the total score In addition multivariant ANOVA demonstrated no significant difference between male and female students in regard to selfdirected learning factors Mean and standard deviation of selfdirecting for all students were 17699 and 2541 respectively Conclusion: R esults showed that selfdirected learning readiness scale has the required validity and reliability to identify selfdirected learning capabilities in Nursing and Midwifery students